Acute Damage to the Sperm Quality and Spermatogenesis in Male Mice Exposed to Curcumin-Loaded Nanoparticles - Xia X (Dove Medical Press, 2020)
Xiaoyu Xia,1,* Li Wang,1,* Xiao Yang,2 Yanqin Hu,1 Qiang Liu1 1Shanghai Key Laboratory of Reproductive Medicine, Department of Histoembryology, Genetics and Developmental Biology, Shanghai Jiao Tong University School of Medicine, Shanghai 200025, People’s Republic of China; 2Shanghai Key Laboratory of Orthopedic Implants, Department of Orthopedics, Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang LiuDepartment of Histoembryology, Genetics and Developmental Biology, Shanghai Jiao Tong University School of Medicine, 280 South Chongqing Road, Shanghai 200025, People’s Republic of ChinaTel +86 21 63846590 Ext. 776761Email qliu0122@shsmu.edu.cnBackground: Curcumin has shown many pharmacological activities in both preclinical and clinical studies. Many technologies have been developed and applied to improve the solubility and bioavailability of curcumin, especially the nanotechnology-based delivery systems. However, there has been evidence that certain nanoparticles have potential reproductive toxicity in practice.Methods: Curcumin-poly (lactic-co-glycolic acid) (PLGA)-PEG nanoparticles (Cur-PLGA-NPs for short) were prepared. The Cur-PLGA-NPs were evaluated with its effect on the proliferation of mouse testicular cell lines in vitro and spermatogenesis in vivo, while PLGA-NPs were used as control. For animal experiments, male BALB/c mice were treated with 20 mg/kg of Cur-PLGA-NPs for continuous 10 days via tail vein injection.Results: We found the curcumin nanoparticles suppressed the proliferation of testicular cell lines in vitro. Furthermore, a short-term intravenous delivery of curcumin-loaded nanoparticles could be harmful to the differentiation of spermatogonia, the elongation of spermatids, as well as the motility of mature sperms.Conclusion: In the present study, we disclosed the acute damage on mouse spermatogenesis and sperm parameters by curcumin-loaded nanoparticles. Our results suggested that the reproductive toxicity of nanoformulated curcumin needs to be prudently evaluated before its application.Keywords: nano-curcumin, reproductive toxicity, Sertoli cell, sperm motility, spermatogenesis